Optimization: From Its Inception - Magnanti, Thomas L. (Management Science, 2021)
Optimization has been one of the most fundamental and extensive contributions of management science/operations research, with an enormous number of contributions and subfields developed by many researchers and practitioners. When the journal Management Science launched in 1954, little was known about optimization, including some results in nonlinear optimization and the simplex method and duality developed for linear programming. However, linear programming computations were limited to problems with at most 101 linear constraints. Then some early contributions by seminal researchers began to develop foundations for the field. I will review a few of these early contributions, focusing on the traveling sales problem and integer programming, decomposition, and column generation. I will summarize some research and applied contributions since then, including the enormous development of computations. I will focus on linear and integer programs with some material on combinatorial optimization. This paper was accepted by David Simchi-Levi, Special Section of Management Science: 65th Anniversary.